1990
DOI: 10.1159/000125605
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine in Rat Hypophysial Portal Blood Is Derived Mainly from the Adrenal Medulla

Abstract: This study was performed to determine if epinephrine (EPI) present in hypophysial portal blood has a peripheral or a central origin. Pituitary stalk and femoral arterial EPI plasma levels were simultaneously measured in rats anesthetized with thiopental or urethane. EPI was measured by two different methods: radioenzymatic assay or HPLC followed by electrochemical detection. In thiopental-anesthetized rats, levels were higher in hypophysial portal than in femoral arterial plasma with both methods. In urethane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The authors found that adrenal demedullation of rats in midlactation did not alter the basal levels of oxytocin, but markedly enhanced the suckling-induced release of oxytocin, suggesting an inhibitory action of adrenal catecholamine at the central level and/or neurohypophysis. It was also documented that the hypophysial portal epinephrine plasma concentration is highly dependent on an adrenal source (Pesce et al, 1990).…”
Section: Noradrenergic Controlmentioning
confidence: 99%
“…The authors found that adrenal demedullation of rats in midlactation did not alter the basal levels of oxytocin, but markedly enhanced the suckling-induced release of oxytocin, suggesting an inhibitory action of adrenal catecholamine at the central level and/or neurohypophysis. It was also documented that the hypophysial portal epinephrine plasma concentration is highly dependent on an adrenal source (Pesce et al, 1990).…”
Section: Noradrenergic Controlmentioning
confidence: 99%